Effects of 4 weeks of device-induced normobaric intermittent hypoxia/hyperoxia training on the performance of elite cyclists: A pilot study - Christoph Peprnicek; Julian Moser; Barbara Wessner (Bern Open Publishing, 2024)
Introduction & Purpose Classic altitude training and other forms of hypoxia are regularly used in endurance training (Mujika et al., 2019). Due to corona exit restrictions in 2019-2020, device-induced normobaric hypoxia/hyperoxia was suggested as an alternative to classic altitude training. Intermittent hypoxia/hyperoxia training (IHHT) has been studied and used in various forms since the 1940s (Serebrovskaya, 2002) with the advantage to be used at the athlete's training site (Burtscher, 2005). The aim of this pilot study was to test the effects of a IHHT intervention on aerobic performance, hematological parameters and hypoxia-induced factor-1α (HIF-1α). Method A total of 11 athletes (2 women) from the U23 and elite national squads of the Austrian Cycling Federation completed 16 IHHT units in addition to their normal training program over a period of 4 weeks as part of a randomized cross over intervention study (control - IHHT, IHHT - control). The IHHT units were carried out on a Cellgym CellAir® Gecko Plus device at rest without exercise following a predetermined protocol (Sessions 1-8: 5 min of hypoxia (12.0% oxygen) followed by 3 min of hyperoxia (34.0% oxygen) repeated five times. Sessions 9-16): 6 min of hypoxia (11.0% oxygen) followed by 3 min of hyperoxia (34.0% oxygen). During the 4 weeks of control period, participants should maintain their training schedule. Aerobic performance was determined before and after the intervention by spiroergometry. As secondary outcomes, changes in hematological parameters and protein levels of HIF-1α were determined from venous blood which was processed immediately after collection. Serum was stored at -80 °C until HIF-1 α determination by ELISA technique. Results Eleven out of 13 athletes took part in the pre - post IHHT measurements, but only three of them managed to participate in the measurements planned for the control period, making it impossible to compare the two conditions. Replacement was not possible due to the availability of candidates and the ongoing preparation for the season. After 4 weeks of intervention with 16 IHHT training sessions, no significant changes were observed in performance parameters such as VO2peak, relative VO2max, maximum power (watts) or threshold values (p > 0.05). There were also no significant changes in blood enzymes, lipid and iron metabolism (p > 0.05). However, a tendency towards increased values of haemoglobin (z = 1.738; p = 0.082) and a significant increase of erythrocyte counts (z = 2.193; p = 0.028) were detected. Other haematological parameters and HIF-1α did not change significantly (p > 0.05). Discussion & Conclusion In summary, four weeks of device-induced normobaric IHHT had a modest effect on haematological parameters, but with no detectable transfer to maximal or submaximal endurance performance in highly trained athletes. Although various studies have shown that the difference between normobaric and hypobaric hypoxia exposure is not limited to the partial pressure of oxygen, but Mounier and Brugniaux state that the physiological responses are in fact equivalent (Mounier & Brugniaux, 2012). However, due to the limitations of the competitive setting and the low sample size, the final interpretation of the study remains difficult. References Burtscher, M. (2005). Intermittierende Hypoxie: Höhenvorbereitung, Training, Therapie [Intermittent hypoxia: altitude preparation, training, therapy]. Schweizerische Zeitschrift für Sportmedizin und Sporttraumatologie, 53(2), 61-67. Serebrovskaya, T. V. (2002). Intermittent hypoxia research in the former Soviet Union and the commonwealth of independent states: History and review of the concept and selected applications. High Altitude Medicine & Biology, 3(2), 205-221. https://doi.org/10.1089/15270290260131939 Mounier, R., & Brugniaux, J. V. (2012). Counterpoint: Hypobaric hypoxia does not induce different responses from normobaric hypoxia. Journal of Applied Physiology, 112(10), 1784-1786. https://doi.org/10.1152/japplphysiol.00067.2012a Mujika, I., Sharma, A. P., & Stellingwerff, T. (2019). Contemporary periodization of altitude training for elite endurance athletes: A narrative review. Sports Medicine, 49, 1651-1669. https://doi.org/10.1007/s40279-019-01165-y